Performativitas Maskulinitas, Hubungan Parasosial, dan Partisipasi Penonton pada Youtube Livestream Bigmo - Regita Amanda Putri; Camelya Rayqah Ibrahim; Garviona Elora Sekar Dewata; Putu Silvia Sloka Sarasamuscaya (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2026)
YouTube Live streaming in Indonesia has developed as a performative space where identity and gender relations are negotiated in real time. This study aims to understand the role of audiences in shaping Bigmo’s masculinity as a streamer, as well as the interaction dynamics between the streamer, audiences, and women during Live broadcasts. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews selected using purposive sampling and analyzed using thematic analysis. The findings show that Bigmo’s masculinity is not fixed, but is collectively formed through interactions with audiences. Comments, challenges, and jokes in the Live chat encourage Bigmo to display confidence, dominance, and risk-taking behavior during Live streaming sessions. The presence of women strengthens Bigmo’s masculine image, but at the same time reveals gender bias through audience comments. Parasocial relationships increase audience involvement in Live streaming and contribute to shaping Bigmo’s persona. This study concludes that YouTube Live streaming functions as a collaborative social space that shapes the construction of digital masculinity.